Misunderstanding of Polygamy Verses in the Qur’an - Darna Daming; Achmad Abubakar; Muhsin Mahfudz; St. Aminah (LPPM IAIN Parepare, 2021)
Lots of misunderstandings in addressing the current practice of polygamy, including faults in interpreting the verses of polygamy in the Qur’anic and misunderstandings in addressing the practice of polygamy by the Prophet Muhammad. This study examines the Qur’anic verses about polygamy and their respective interpretations, and how they relate to the current practice of polygamy. In addition, it also equipped this article with a discussion of the views of Islamic law and positive Indonesian law on polygamy, as well as the impact of polygamy on social life. The results of the study show that the principle of marriage in the concept of the Qur’anic and positive law in Indonesia is to adhere to a monogamous marriage system. The permissibility of polygamy is an obligation that is complicated and tightened and only for people who really need it in a very emergency and accompanied by the condition that they can do justice between wives. Prophet Mohammad Saw. did polygamy not because of sexual motivation, but because of religious, social, and humanitarian motivations. There are two wisdoms behind the Prophet Saw. practicing polygamy, namely to support the widows of war victims and as one of the Prophet’s political strategies to unite dispersed and hostile groups.